Differentiation in prefrontal cortex recruitment during childhood: Evidence from cognitive control demands and social contexts. (April 2019) - Chevalier, Nicolas; Jackson, Judith; Revueltas Roux, Alexia; Moriguchi, Yusuke; Auyeung, Bonnie
Highlights: Using fNIRS, we examined how children recruit PFC while engaging cognitive control. Activation increased with cognitive control demands more in left than right PFC. It was higher in left PFC in competitive than cooperative contexts, and in right PFC in cooperative and neutral compared to competitive contexts. Older children showed greater variations in PFC activation than younger children. Cognitive control is supported by more differentiated PFC recruitment with age. Abstract: Emerging cognitive control during childhood is largely supported by the development of distributed neural networks in which the prefrontal cortex (PFC) is central. The present study used fNIRS to examine how PFC is recruited to support cognitive control in 5–6 and 8-9-year-old children, by (a) progressively increasing cognitive control demands within the same task, and (b) manipulating the social context in which the task was performed (neutral, cooperative, or competitive), a factor that has been shown to influence cognitive control. Activation increased more in left than right PFC with cognitive control demands, a pattern which was more pronounced in older than younger children. In addition, activation was higher in left PFC in competitive than cooperative contexts, and higher in right PFC in cooperative and neutral than competitive contexts. These findings suggest that increasingly efficient cognitive control during childhood is supported by more differentiated recruitment of PFC as a function of cognitive control demands with age.